2008
DOI: 10.1111/j.1937-8327.2007.tb00432.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Truck Drivers and their Job Performance Regarding Highway Safety

Abstract: Limited research has addressed the issue of truckdrivers and their performance regarding highway safety in terms of reduced number of crashes per driver. The primary purpose of this study was to determine how tractor trailer truck drivers' job performance could be improved while at the same time ensuring increased revenue for the transportation companies employing them. The target population for this study comprised of tractor‐trailer truck drivers employed by a leading transportation company in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Safety training ranges from education about road conditions, speeding, braking, and weight distribution to discussion of driver distraction, fatigue, and physical, mental, and emotional health (Staplin, Gish, Decina, & Brewster, 2003). Studies of safety, then, typically focus on harm by estimating the effects of these variables on crash rates in order to measure the degree of safety present within a specific carrier (Nafukho et al, 2007;Nafukho & Hinton, 2003). Given that crashes and their associated costs are the most relevant outcome regarding transportation safety, the number of crashes or the probability of a crash over a given distance or within a specified time frame is the most common method of quantifying safety.…”
Section: Literature Review Defining and Measuring Highway Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Safety training ranges from education about road conditions, speeding, braking, and weight distribution to discussion of driver distraction, fatigue, and physical, mental, and emotional health (Staplin, Gish, Decina, & Brewster, 2003). Studies of safety, then, typically focus on harm by estimating the effects of these variables on crash rates in order to measure the degree of safety present within a specific carrier (Nafukho et al, 2007;Nafukho & Hinton, 2003). Given that crashes and their associated costs are the most relevant outcome regarding transportation safety, the number of crashes or the probability of a crash over a given distance or within a specified time frame is the most common method of quantifying safety.…”
Section: Literature Review Defining and Measuring Highway Safetymentioning
confidence: 99%
“…Furthermore, evidence of previous studies offers convincing rationale for the inclusion of the primary factors within the working model (see Figure 1) shown in this article. For example, earlier transportation studies investigated some elements of driver-dispatcher relations (Keller & Ozment, 1999;Taylor, 1991), job satisfaction and attitudes (McElroy, Rodriguez, Griffin, Morrow, & Wilson, 1993), relationships with customers, driver turnover, and driver performance (Keller, 2002), human resource management practices that influence quit rates (Min & Lambert, 2002;Shaw, Delery, Jenkins, & Gupta, 1998), and other variables such as fringe benefits, training, career development, time home, salary, bonuses, driver performance, education, and other demographic variables (Gaertner, 2000;Min & Lambert, 2002;Nafukho & Hinton, 2003;Nafukho, Hinton, & Graham, 2007;Richard, LeMay, & Taylor, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, as long-distance truck driving jobs are known to often involve overtime, drivers are accustomed to working overtime, accepting a productivity-based payment method [ 5 ], and adapting to the situation [ 9 ]. In fact, research has also shown that wages in the transport sector motivate drivers to work longer hours [ 10 , 11 ], which can encourage drivers to drive overtime, shorten rest periods (daily and weekly), and manipulate tachographs and driver cards [ 12 ]. However, this type of behavior may be the result by pressures from employers to make as many journeys as possible [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and the conscious, adapted behavior of truck drivers to maximize earnings [ 8 , 9 ].…”
Section: Literature Review and Development Of A Structural Researcmentioning
confidence: 99%
“…In fact, research has also shown that wages in the transport sector motivate drivers to work longer hours [ 10 , 11 ], which can encourage drivers to drive overtime, shorten rest periods (daily and weekly), and manipulate tachographs and driver cards [ 12 ]. However, this type of behavior may be the result by pressures from employers to make as many journeys as possible [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and the conscious, adapted behavior of truck drivers to maximize earnings [ 8 , 9 ]. Thus, our first hypothesis is as follows:…”
Section: Literature Review and Development Of A Structural Researcmentioning
confidence: 99%
“…Rodriguez et al (2006) Jaguar, PWC 2,368 drivers (United States) Study showed a 1% pay increase corresponds to a 1.33% reduction in crash risk probability. Nafukho, Hinton, and Graham (2007) Jaguar, PWC 13,240 drivers (United States) There is a low but positively significant association between salary, miles driven per month and number of crashes.…”
Section: Hunter and Magnummentioning
confidence: 99%